"You are not alone": a qualitative study to explore barriers to ART initiation and implications for a proposed community-based youth treatment club among young adults newly diagnosed with HIV in South Africa. Issue 7 (3rd July 2021) - Nardell, Maria F.; Lee, Yeonsoo Sara; Rousseau, Elzette; Julies, Robin; Klaas, Portia; Vundhla, Prisca; Butler, Lisa; Bassett, Ingrid V.; Mellins, Claude A.; Bekker, Linda-Gail; Katz, Ingrid T.
ABSTRACT: In South Africa, despite universal antiretroviral therapy (ART) availability, 60% of persons living with HIV (PLWH) ages 15–24 are not on treatment. This qualitative study aimed to identify barriers to ART initiation and the implications for a proposed community-based Youth Treatment Club to improve ART initiation for young PLWH in limited-resource, high HIV-prevalence communities in Cape Town, South Africa. Recruiting participants at community testing sites from 2018 to 2019, we conducted semi-structured interviews, informed by Social Action Theory (SAT), with 20 young adults, ages 18- to 24-years-old, newly diagnosed with HIV, along with 10 healthcare providers. Through systematic qualitative analysis, we found that young PLWH face barriers to treatment initiation in three SAT domains: (1) stigmatizing social norms (social regulation processes); (2) challenges coping with a new diagnosis (self-regulation processes); and (3) anticipated stigma in the clinic environment (contextual factors). Participants shared that a proposed community-based Youth Treatment Club for newly diagnosed youth would be an acceptable strategy to promote ART initiation. They emphasized that it should include supportive peers, trained facilitator support for counseling and education, and a youth-friendly environment.